Analisis Spearman Rank pada Persepsi Civitas Akademik Tentang Pelaksanaan dan Dampak Program MBKM - Mulianah, Sri; Tjalla, Awaluddin; Mahdiyah, Mahdiyah (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Kampus merdeka belajar kampus merdeka program (MBKM) is a policy issued by the government as a solution to current problems and developments. This study aims to find a correlation between the implementation of MBKM and the impact of MBKM on the IAIN Parepare academic community. This study is a quantitative study using a correlation method involving the academic community consisting of students, educational staff and educational staff as a population. A perception and readiness questionnaire with a five-point Likert scale was distributed to 100 samples with details of 25 teaching staff (lecturers), 25 educational staff and 50 students via a Google form link distributed via social media (WhatsApp). The collected data was analyzed using the Spearman Rank correlation analysis technique. The results of the study show that lecturers' perceptions are 0.553 times better than education staff's perceptions regarding the implementation of the MBKM program and impact. Student perceptions are 0.507 times better than education staff's perceptions regarding the implementation and impact of the MBKM program.